Losing by winning: The danger zone of adverse competitor replacement - Makadok, Richard; Ross, David Gaddis (Strategic Management Journal, 2018)
[Research summary: We use a formal model, motivated by a case study from the airline industry, to consider an industry structure wherein a firm may find that improving its competitiveness hurts its performance. Specifically, we examine the possibility that a superior incumbent may, by getting stronger, drive a weak rival from the market, and thereby allow a stronger rival to enter in its place. Such "adverse competitor replacement" reduces the profit of the superior incumbent and may even, in an extreme case, cause the superior incumbent to be driven from the market as well. We show that adverse competitor replacement can arise under a rational equilibrium and may become more likely if a firm improves its capability for self-improvement. Managerial summary: Managers are consistently advised to improve the competitiveness of their firms and beat the competition. We examine the possibility that beating out the competition may have adverse consequences. Specifically, a strong incumbent may, by getting stronger, outcompete a weaker rival to such an extent that the weaker rival exits the market, thereby creating an open market niche for a stronger rival to enter, in effect, a form of adverse competitor replacement. Competing with this stronger rival may in turn reduce the strong incumbent's profits below what they had been before driving the weak rival out. We illustrate adverse competitor replacement with a case study from the airline industry and discuss implications for a firm's investment in its own competitiveness.]